Pembuatan Jobsheet Pada Mata Kuliah Prakte Instalasi Listrik Komersil di Universitas Negeri Medan - Zulkhairiansah, Zulkhairiansah; Purba, Sukarman; Sulastri Sitakar, Niken; Fadilah, Aria (Jurnal Etnik: Ekonomi-Teknik, 2023)
To improve the quality of education, the government has added curricula such as the 2013 curriculum and the Independent Learning Curriculum. In order to achieve an effective and efficient learning process, learning can be optimized by developing learning strategies. Achieving this process requires media support and learning resources, either through theory or practice. Therefore researchers are trying to develop an effective and practical commercial electrical practicum Joobsheet that facilitates access to learning resources and reference materials for lecturers and students while increasing students' knowledge, understanding and academic achievement. The research methodology in this study is R and D using a 4D model which involving a sample of 20 Electrical Engineering Education students of UNIMED and 3 professional validators. As a result, media and material experts gave a score of 0.8 which means the commercial electrical installation Jobsheet is effective, and practice experts give a score of 0.92 which means the commercial electrical installation Jobsheet is very practical. Out of 17 students felt the Jobsheet was very practical and 3 students found it practical. Based on this, the researchers concluded that Jobsheets are effective for learning commercial electrical installations.